TATA KELOLA SEKOLAH ALAM KEBUN TUMBUH MENUJU SEKOLAH YANG BERKUALITAS - Dita Rahmaditiani Junaidi; Evi Satispi; Aldira Lindawati; Dalila Afif (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2022)
This research is motivated by the success of phenomenon educational institution based on nature that serve as one of the alternative educational institutions in Indonesia. The success of the phenomenon came from from the ability of sekolah alam to shape and transform the sought-after core values. This research aims to explain the process of forming and transforming core values based on environmental uniqueness and local wisdom at Sekolah Alam Kebun Tumbuh (SAKT) which conducted in August – December 2021, and located in the middle of an urban area. Researcher used a qualitative approach with data collection techniques, interviews, and documentation as well as analysis using interactive model qualitative techniques which included data collection, data reduction, data presentation, and drawing conclusions. The results of the research indicate that all educational and learning activities in sekolah Alam carried out with an integrative holistic approach with nature as a place, source, and learning media in the context of cognitive processes, awareness, enlightenment, empowerment, character building and children's behavior. The core values developed by Sekolah Alam Kebun Tumbuh are based on five values, includes noble character, critical thinking, leadership, entrepreneurial spirit, and toughness. These core values are the hallmark and differentiator from Sekolah Alam Kebun Tumbuh from other sekolah alam as well as the brand image of Sekolah Alam Kebun Tumbuh. In addition, it continues to embody the three dimensions of core values in general, namely curriculum, methods, environment and physics.